Эффективность использования информационных технологии в процессе преподавания философии в высшей школе - Касымсейтова, С.А. (My University, 2016)
This paper emphasizes the need to improve the educational process in high school, analyzed the possibility of the ratio of traditional and innovative in teaching philosophy.
Keywords: higher school; innovations; teaching of philosophy